Approaches Of The Constitutional Court Of The Russian Federation Towards Freedom Of Expression And Freedom Of Assembly - Taribo, Eugenie; Kuznetcov, Dmitrii (The Constitutional Court of the Republic of Indonesia, 2015)
The paper consists of seven sections describing the Constitutional Courtâs practice in respect of freedom of expression and freedom of assembly issues. The matters covered by the paper includes challenges of the constitutionality of laws forbidding civil servants to give public statements, regulation of religious organisations public events, regulation of restricted urban areas where freedom of assembly is limited, the content-based restrictions in respect of LGBT-speech.